THE QUALITY IMPROVEMENT PROCESS THROUGH APPLICATION OF MULTI-VARI CHART IN AN AUTOMOTIVE SUPPLIER - (:unkn) unknown (TECHNICAL UNIV CLUJ-NAPOCA, 2014)
In today's competitive market, manufacturers have to produce products that meet the customer needs and expectations, by optimally balancing the quality, time and cost parameters. To accomplish this, manufacturers have to establish the modern quality management systems and standardization. It is inevitable to apply the modern quality management systems as well as geometric product identification and validation tolerances (GPS) to develop, design, produce and verify a product. There are statistical methods and quality management systems which were developed in the last century for the implementation of process improvements. The main objective of this study is to apply GPS (Geometrical Product Specification) to the Turkish automotive supplier industry by using the Shainin Design of experiment method's tool of Multi-Vari Chart. Multi-Vari Chart is a tool which can be understood and applied easily. It is realized on the basis of modern quality management systems and GPS. The implementation of this method has a great importance on the effectiveness and efficiency of the product systems.
Keywords: Process Improvement; Multi-Vari Chart; Geometrical Product Specification (GPS); Quality Management System